E-Learning of English Subject Using Demonstration Discussion Method at MAN 2 Solok - Ratih Purwasih; Wahyudi; Liranti Rahmelina; Melya Ramadina (Gayaku Publisher, 2023)
MAN 2 Solok is one of the levels of formal secondary education in West Sumatra. Until now, online learning still uses the WhatsApp platform and occasionally uses Google Meet, so there is a need for an E-Learning system to optimize more structured and interactive learning media between students and teachers at MAN 2 Solok. Thus, the aim of this research is to design an E-Learning system for learning, especially English, based on the Discussion Demonstration method. The system design method used is waterfall with four phases, namely requirements analysis, design, coding, testing. The E-learning system was created using the PHP programming language and the database uses MySQL. The result of this research is a design for an E-Learning system for English Language Subjects Based on the Demonstration Discussion Method at MAN 2 Solok. Thus, the existence of this E learning system will make it easier for teachers and students to access materials, exercises or interactive quizzes in English learning, so as to improve students' abilities in English subjects.